Medication Overuse Headaches among Children—The Contribution of Migraine and TTH - Jacob Genizi; Morya Shnaider; Liat Yaniv; Nogah C. Kerem; Keren Nathan; Irina Chistyakov (Life, 2023)
Medication overuse headaches are a frequent phenomenon observed in individuals suffering from chronic headaches. It arises due to the excessive consumption of pain-relief medications, resulting in the escalation and continuous persistence of headache symptoms. Nevertheless, the prevalence and distinctive characteristics of medication overuse headaches in the pediatric population have not been comprehensively explored. The primary objective of this research is to delineate the features of medication overuse headaches in children, particularly emphasizing the investigation of its epidemiology and the diagnostic patterns for headaches. We conducted a retrospective study and analyzed the medical records of children and adolescents who were evaluated at the outpatient pediatric headache clinic at the Bnai Zion Medical Center for headaches during the period spanning 2007 to 2017. Our study encompassed a cohort of 1008 patients experiencing headaches. Among these participants, 268 individuals (26.6%) were diagnosed with migraine, 250 (24.8%) exhibited tension-type headaches (TTH), and 490 (48.6%) were classified as having undifferentiated headaches. Out of the whole group, 65 had chronic headaches: 35 (54%) with migraine, 20 (30%) with tension-type headaches (TTH), and 10 (15%) with the undifferentiated headache of childhood, with the majority (73%) being female. In summary, medication overuse headaches are a prevalent issue among children grappling with chronic headaches. Intriguingly, they appear to be more pronounced within the tension-type headache (TTH) group compared to migraine sufferers and exhibit a higher prevalence among females. This study underscores the significance of early detection and careful management of medication overuse headaches in pediatric cases, shedding light on its distinct characteristics in the realm of childhood headache disorders. Further research is warranted to elucidate the underlying factors contributing to the observed gender disparity and the distinct prevalence rates among different headache subtypes.